Organization of antennal lobe-associated neurons in adult Drosophila melanogaster brain. - Tanaka, N.K.; Endo, K.; Ito, K. (Journal of Comparative Neurology, 2012)
The primary olfactory centers of both vertebrates and insects are characterized by glomerular structure. Each glomerulus receives sensory input from a specific type of olfactory sensory neurons, creating a topographic map of the odor quality. The primary olfactory center is also innervated by various types of neurons such as local neurons, output projection neurons (PNs), and centrifugal neurons from higher brain regions. Although recent studies have revealed how olfactory sensory input is conveyed to each glomerulus, it still remains unclear how the information is integrated and conveyed to other brain areas. By using the GAL4 enhancer-trap system, we conducted a systematic mapping of the neurons associated with the primary olfactory center of Drosophila, the antennal lobe (AL). We identified in total 29 types of neurons, among which 13 are newly identified in the present study. Analyses of arborizations of these neurons in the AL revealed how glomeruli are linked with each other, how different PNs link these glomeruli with multiple secondary sites, and how these secondary sites are organized by the projections of the AL-associated neurons.